Analysis of the prediction of the suitable distribution of Polygonatum kingianum under different climatic conditions based on the MaxEnt model - Guo, Yixin; Zhang, Shiyan; Tang, Shicheng; Pan, Jianying; Ren, Linghui; Tian, Xin; Sun, Zhirong; Zhang, Zilong (Frontiers in Earth Science, 2023)
Environmental changes have led to changes in the suitable areas for growing certain medicinal plants, which might lead to changes in cultivation areas and quality of medicinal materials. Polygonatum kingianum is a commonly used medicinal plant and, with its growing demand, the sustainable development of P. kingianum is particularly important. Therefore, this study comprehensively considered environmental variables, such as climate, soil, and topography, collected 181 valid distribution records, and used the MaxEnt to predict and evaluate the changes and potential distribution of P. kingianum. The results showed that the current high-suitability areas (31,534.60 km2) for this medicinal plant are mainly distributed in the southern part of Yunnan Province, western part of Guangxi Province, and southwestern part of southwestern Guizhou Province. Under a future climate change scenario, the area of suitable habitats showed a trend of first expansion and then contraction, but the overall trend still expanded. The medicinal plant’s migration trend to the northwest of Guizhou Province and northeast of Yunnan Province was more clear. At the Chinese scale, temperature and precipitation were the important factors affecting the medicinal plant’s distribution. At the national scale, Bio7, Bio12, Bio17, Bio11, S_USDA_TEX_CLASS, and Elevation were key variables affecting P. kingianum distribution, whose cumulative value of percent contribution was 93.6%. At a more precise scale, precipitation, soil variables, and altitude became the key factors affecting its distribution. Among them, S_USDA_TEX_CLASS has the highest contribution rate. Overall, the results of this study provided a reference for the determination of suitable planting areas of P. kingianum in China.